A triplet biradical with double bidentate sites based on tert-butyl pyridyl nitroxide as a candidate for strong ferromagnetic couplers. (15th October 2018) - Okazawa, Atsushi; Terakado, Yutaro; Ishida, Takayuki; Kojima, Norimichi
Abstract : A new triplet biradical having two chelatable nitroxide sites and a strong intramolecular ferromagnetic coupling through a " meta – para " bipyridyl linker. Abstract : We synthesised a new biradical, 34bpybNO, having two chelating radical sites and demonstrated its crystal structure and ground triplet nature. Frozen-solution magnetic measurement and electron spin resonance results revealed a strong intramolecular ferromagnetic coupling reaching 2 J / k B = ∼+170 K, which is supported by density functional theory calculations.